Coupling thermal atomic vapor to an integrated ring resonator - R Ritter; N Gruhler; W H P Pernice; H Kübler; T Pfau; R Löw (New Journal of Physics, 2016)
Strongly interacting atom–cavity systems within a network with many nodes constitute a possible realization for a quantum internet which allows for quantum communication and computation on the same platform. To implement such large-scale quantum networks, nanophotonic resonators are promising candidates because they can be scalably fabricated and interconnected with waveguides and optical fibers. By integrating arrays of ring resonators into a vapor cell we show that thermal rubidium atoms above room temperature can be coupled to photonic cavities as building blocks for chip-scale hybrid circuits. Although strong coupling is not yet achieved in this first realization, our approach provides a key step towards miniaturization and scalability of atom–cavity systems.